Interfacial engineering of hole transport layers with metal and dielectric nanoparticles for efficient perovskite solar cells - Wang, D.; Chan, K.; Elumalai, Naveen Kumar; Mahmud, M.; Upama, M.; Uddin, A.; Pillai, S. (R S C Publications, 2017)
In this work, we have demonstrated the incorporation of metal (Ag NPs) and dielectric nanoparticles (SiO2 NPs) into the hole transporting layers of inverted PSCs using facile deposition methods. Interfacial engineering in PSCs is accomplished by incorporating 50 nm Ag NPs or SiO2 NPs within the PEDOT:PSS interlayer. Dielectric SiO2 NPs were used for comparison purposes as a control sample to isolate morphological impacts without plasmonic effects. The photovoltaic performance of the devices significantly improved due to increased charge selectivity and enhanced charge collection properties across the interface (HTL). The recombination resistance of the SiO2 NP incorporated HTL based PSCs was 193% higher than that of the conventional devices. In-depth analysis using impedance measurements revealed that devices containing Ag or SiO2 NPs have low electrode polarization and consequently lower charge accumulation at the interface. Lower electrode polarization in the modified devices was also found to improve the charge carrier selectivity, which eventually led to enhanced fill factor and lower parasitic resistances. Interfacial engineering via NPs yielded improvements in the electrical characteristics of non-optical origin, which not only enhanced device performance, but also reduced the hysteresis effects to much lower than in the conventional inverted PSCs based on a pristine PEDOT:PSS interlayer.